Protest music as an instrument for communicating social discontent in Africa (2017)
Several people in Africa are discontent with the nature of governance, leadership and socioeconomic issues that plague the continent. These grievances are expressed through protest music, which draws attention to human dissatisfaction due to colonial and post-colonial oppressive rule. As a critical communication genre, protest music depicts the elites as architects of socioeconomic degradation. The paper examines socio-political climate in selected African countries. It describes the nature and relationships among governance, social discontent and protest music. Through contextual analysis, the paper identifies music as a medium of resistance communication. While it adopted Agenda Setting theory, purposive and available sampling techniques were used to select the relevant countries and songs. Findings reveal that protest music was strategically used in Nigeria and South Africa to unravel issues of social discontent. The genre operates as an information processing channel and socio-political commentary that offers the state knowledge about distasteful governance and opportunities to redress, adjust, amend and solidify good governance in affected countries. The analysis shows that protest music is context-specific and isused as an instrument for communicating social discontent in selected African countries.